2021
DOI: 10.1186/s13046-021-02104-4
|View full text |Cite|
|
Sign up to set email alerts
|

Embedding similarities between embryos and circulating tumor cells: fundamentals of abortifacients used for cancer metastasis chemoprevention

Abstract: Background The global epidemiological studies reported lower cancer risk after long-term use of contraceptives. Our systematic studies demonstrated that abortifacients are effective in preventing cancer metastases induced by circulating tumor cells (CTCs). However, the molecular and cellular mechanisms by which abortifacients prevent CTC-based cancer metastases are almost unknown. The present studies were designed to interdisciplinarily explore similarities and differences between embryo implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Blastocyst implantation is a complex process including attachment of the blastocyst to the receptive endometrium and invasion of the trophoblastic cells of the conceptus into the endometrium and basement membrane. 189 After analysing the molecular and cellular similarities and differences between embryonic implantation to uterine endometrium and breast CTC adhesion to vascular endothelium, 190 we found that many biological factors were shared by both the embryonic implantation system and CTC adhesion-invasion system, including integrins, cellular adhesion molecules (CAM), such as EpCAM, ICAM, VCAM, and selectin, hormone receptors, sialyl Lewis X and MMPs. 112 The in vivo inhibition by abortifacients of both embryo implantation to uterus and CTC metastasis to lung further revealed similarities in molecular and cellular embedding between the reproduction system and cancer metastases, and provided fundamentals for abortifacients to intervene CTC adhesion/invasion to the distant metastatic organs in vivo.…”
Section: Cell Surfactant Concept and Practicesmentioning
confidence: 99%
“…Blastocyst implantation is a complex process including attachment of the blastocyst to the receptive endometrium and invasion of the trophoblastic cells of the conceptus into the endometrium and basement membrane. 189 After analysing the molecular and cellular similarities and differences between embryonic implantation to uterine endometrium and breast CTC adhesion to vascular endothelium, 190 we found that many biological factors were shared by both the embryonic implantation system and CTC adhesion-invasion system, including integrins, cellular adhesion molecules (CAM), such as EpCAM, ICAM, VCAM, and selectin, hormone receptors, sialyl Lewis X and MMPs. 112 The in vivo inhibition by abortifacients of both embryo implantation to uterus and CTC metastasis to lung further revealed similarities in molecular and cellular embedding between the reproduction system and cancer metastases, and provided fundamentals for abortifacients to intervene CTC adhesion/invasion to the distant metastatic organs in vivo.…”
Section: Cell Surfactant Concept and Practicesmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], an error was found in the Author’s contributions section. The correct details should read as:…”
mentioning
confidence: 99%